A case of arthrogryposis in a buffalo calf causing dystocia - MAHAJAN, AMIT; SATHYA, A; SINGH, PRAHLAD; PRABHAKAR, S (The Indian Journal of Animal Reproduction, 2023)
In the present case, dystocia due to foetal Arthrogryposis and its malposture was relieved by foetotomy.
Keywords: Buffalo; fetus; arthrogryposis